Solar powered peltier cooling storage for vaccines in rural areas - Henning Buitendach; Immanuel Ninma Jiya; Rupert Gouws (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The research presented in this paper proposes a new design of a vaccine cooling and storage unit that can keep vaccines in the cold chain (2°C to 8°C). This design was done to facilitate effective completion of the African vaccination week. The cooling and storage unit was designed to be compact, portable, well isolated and to make use of a PV solar energy system as a source of electricity. The cooling unit makes use of a Liquid to Air thermoelectric cooling module connected to some tubing and a liquid pump to cool the inside of the cooling unit. The design process also included designing a control system that controls the temperature inside the cooling holder and a monitoring system to monitor the battery voltage and capacity. The system also has a user interface that displays the temperatures inside and outside of the cooling holder, as well as the battery voltage and capacity. The cooling system successfully developed was able to keep vaccines in the cold chain for up to three days, the system could control the temperature of the vaccines with an accuracy of 1°C and was small and portable, but still had enough room to house up to 250 vaccines.